(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
Has been conducted a research of dose determination of effectiveness extract of Lawsonia inermis L. as anti-inflammatory on Rattus norvegicus. The purpose of this research is to gain an in depth understanding of effective dose of Lawsonia inermis L. as anti-inflammatory toward the reduction time of swelling on Rattus norvegicus’ feet .The method which being used was carrageenan induced on Rattus norvegicus’ feet. Rattus norvegicus were devided to 6 (six) group which a group as negative control was given sodium CMC orally, a group as positive control was given Sodium Diclofenac orally, and 4 (four) as test was given extract with 4 doses variation (50mg/kg, 100mg/kg, 150 mg/kg, and 200 mg/kg) orally to each of mice that has pre-conditioned to swell on its foot. The result shows that T-Count is bigger than T-Table with significant standart 0,05 and smaller than T-Table with significant standart 0,01. It proves that there is significant difference between sodium diclofenac and extract of Lawsonia inermis L in 100mg/kgBW. That concludes that extract of Lawsonia inermis L. has anti-inflammatory effect with effective dose as anti-inflammatory in 100mg/kg.